Surgical versus non-surgical treatment of actinic cheilitis: A systematic review and meta-analysis - Carvalho, Marianne de Vasconcelos; de Moraes, Sandra Lúcia Dantas; Lemos, Cleidiel Aparecido Araujo [UNESP]; Santiago Júnior, Joel Ferreira; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP] (Wiley, 2019)
Objective: The aim of this systematic review was to compare outcomes between surgical and non-surgical treatment of actinic cheilitis (AC). Materials and Methods: A systematic review and meta-analysis based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses guideline were performed. A search of PubMed/MEDLINE, Web of Science, and Cochrane Library databases was conducted. Articles were selected based on the inclusion criteria: randomized clinical trials, prospective/retrospective studies, and case series with at least 10 patients, with a minimum follow-up period of 6 months. A weighted remission rate (RER) and recurrence rate (RR) with a 95% confidence interval was performed. Data analysis was performed using a comprehensive meta-analysis software. Results: A total of 283 ACs in 10 studies were included. About 2.5% surgically treated cases underwent malignant transformation. The weighted remission rate was higher for surgical (92.8%) compared to non-surgical treatment (65.9%). The recurrence rate was lower for surgical (8.4%) compared to non-surgical treatment (19.2%). Conclusion: In this systematic review, the surgical treatment was more favorable than non-surgical for AC. Meanwhile, further studies are needed that should maximize methodological standardization and have greater rigor of the data collection process.
Keywords: actinic cheilitis; intervention; management